2020
DOI: 10.3390/en13153906
|View full text |Cite
|
Sign up to set email alerts
|

A Photovoltaic Power Curtailment Method for Operation on Both Sides of the Power-Voltage Curve

Abstract: Massive integration of non-dispatchable energy into electric power systems is a challenging task. Electric power systems are becoming increasingly vulnerable in terms of frequency stability, as renewable energy displaces conventional synchronous generation from the energy mix. For this reason, grid codes are starting to demand different ancillary services from renewable generators, such as frequency control. In contrast to wind generators, which can deliver to the grid part of the kinetic energy stored in thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
(30 reference statements)
0
14
0
Order By: Relevance
“…The possibility of operating the PV system suboptimally on both the left and right sides of the P-V curve was introduced in [30]. This work also demonstrated that real-time estimation of irradiance and temperature highly depends on the operation side.…”
Section: Methods Based On Maximum Power Point Estimationmentioning
confidence: 94%
“…The possibility of operating the PV system suboptimally on both the left and right sides of the P-V curve was introduced in [30]. This work also demonstrated that real-time estimation of irradiance and temperature highly depends on the operation side.…”
Section: Methods Based On Maximum Power Point Estimationmentioning
confidence: 94%
“…At this point, the engineers only rely on technical competence [59][60][61]. The new gas-to-liquid plant and shale gas exploitation were estimated to create 90 000 and 2 575 jobs respectively in the IEP by 2040, but they are no longer considered economically viable options [62,63]. Instead, technological developments such as electrification of transport, the use of hydrogen-based power in industry, electrical storage, and distributed energy generation are currently seen as economically viable options [35].…”
Section: Potential Job Creationmentioning
confidence: 99%
“…Power curtailment (Cr) and energy storage are among these strategies. It is undeniable that energy storage system implementation costs are high [3] while power Cr is a more feasible method for forcing a planned output reduction in order to balance the supply and demand for electricity [4], [5].…”
Section: Introductionmentioning
confidence: 99%